Sex Differences in Self-Reported Hip Function Up to 2 Years After Arthroscopic Surgery for Femoroacetabular Impingement. (January 2016) - Joseph, Roody; Pan, Xueliang; Cenkus, Kathleen; Brown, Lindsey; Ellis, Thomas; Di Stasi, Stephanie
Background: Femoroacetabular impingement (FAI) is a significant cause of disability in young adults. Hip arthroscopic surgery restores bony congruence and improves function in the majority of patients, but recent evidence indicates that women may experience worse pre- and postoperative function than men. Purpose/Hypothesis: The purpose of this study was to identify whether self-reported hip function differed between men and women with symptomatic FAI. The hypothesis was that mean self-reported hip function scores would improve after arthroscopic surgery but that women would report poorer function than men both before and up to 2 years after arthroscopic surgery. Study Design: Cohort study; Level of evidence, 2. Methods: A total of 229 patients (68.4% women; mean [±SD] age, 31.6 ± 10.8 years; mean [±SD] body mass index, 26.8 ± 11.9 kg/m 2 ) underwent hip arthroscopic surgery for unilateral symptomatic FAI. All eligible and consenting patients with radiologically and clinically confirmed FAI completed the International Hip Outcome Tool (iHOT-33) and the Hip Outcome Score activities of daily living subscale (HOS-ADL) before hip arthroscopic surgery and at 3, 6, 12, and 24 months after arthroscopic surgery. A linear mixed model for repeated measures was used to test for differences in self-reported hip function between men and women over the study period ( P ≤ .05). Results: There were no significant time × sex interactions for either the HOS-ADL ( P = .12) or iHOT-33 ( P = .64), but both measures showed significant improvements between the preoperative time point and each of the 4 follow-up points ( P < .0001); however, self-reported hip function did not improve between 6 and 24 months after arthroscopic surgery ( P ≥ .11). Post hoc independent t tests indicated that women reported poorer hip function than did men before surgery ( P ≤ .003) both on the HOS-ADL (mean ± standard error of the mean [SEM], 67.4 ± 1.9 [men] vs 60.5 ± 1.3 [women]) and iHOT-33 (mean ± SEM, 38.0 ± 1.9 [men] vs 30.9 ± 1.3 [women]); scores were not different between sexes at any other time point. Conclusion: These findings indicate improvements in self-reported hip function in patients with FAI, regardless of sex, until 6 months after hip arthroscopic surgery. Although women reported poorer preoperative function than did men, the differences were not significant 2 years after surgery.